CALIBRATION OF METHANE ANALYSIS BY RAMAN SPECTROSCOPY IN H2O-NACL-CH4 FLUID INCLUSIONS - Guillaume D.; Teinturier S.; Dubessy J.; Pironon J. (My University, 2003)
Calibration of the determination of CH4/H2O ratio using Raman spectroscopy is carried out using synthetic fluid inclusions at different NaCl concentration (0, 0.05, 0.66, 0.98, 1.00, 1.60, 2.25 and 3.5 m NaCl). Spectra of the stretching bands of methane and water in the aqueous phase were collected at variable temperatures up to a few degrees above the homogenisation temperature. The composition of the aqueous phase for temperatures below the homogenisation temperature was calculated with a computer program, using the model of Duan et al. [Geochim. Cosmochim. Acta 56 (1992) 1451]. Results show the dependency of the estimate of the CH4 concentration on salinity: at constant CH4 concentration, the CH4/H2O area ratio of Raman bands decreases with increasing salinity from 0 to 1.6 m and remains constant up to 3.5 m NaCl. The P–T projection of the isopleth of a natural fluid inclusion is deduced from the homogenisation temperature, its composition obtained from cryometry (mNaCl eq.) and Raman analysis (mCH4) ratio. This methodology was applied to a sample from the Cave-in-Rock MVT deposit (fluorite–Pb–Zn district, southern Illinois, USA) presenting petroleum fluid inclusions associated with fluid inclusions of the system H2O–NaCl–CH4. Hydrocarbon isochore intersects the isopleth of the H2O–NaCl–CH4 inclusions at the homogenization temperature, which validates this procedure.
Keywords: Fluid inclusions; H2O–CH4 –NaCl system; Methane analysis; Raman spectroscopy; Petroleum fluid inclusions; Diagenetic fluids